PERBEDAAN PENGARUH LATIHAN METODE BERMAIN DAN SIRKUIT TERHADAP PENINGKATAN KEBUGARAN JASMANI (Studi Eksperimen Pada Siswa SMP Negeri 9 Padang) - Yusep Efendi, Argantos (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
The problem in this research is the low degree of physical fitness of students of Padang State Junior High School 9. It is caused by many factors and one of them caused by the training methods used in the learning process of physical education. One effort to increase the degree of physical fitness of students of Padang State Junior High School 9 is with the selection of training methods effectively and efficiently. Therefore, this study aims to look at the differences in the effects of exercise play method and circuit to increase physical fitness of students of Padang State Junior High School 9.The method used in this study is a quasi-experiment (quasi-experiment). The population in this study were male student Padang State Junior High School 9 in the academic year 2015/2016 used were as many as 66 people. The sampling technique is done by proportional random sampling, the number of samples used as many as 32 people. Data collection techniques using test instruments Physical Freshness Indonesia (TKJI) and statistically analyzed using comparative test (t-test) at significance level of 5%.The results of this study indicate that: (1) Training methods play a significant influence on improvement of physical fitness of students of Padang State Junior High School 9, the results show that tcount (3.971) > ttable (1.753). (2) Exercise circuit method significantly influence the improvement of physical fitness of students of Padang State Junior High School 9, the results show that tcount (3.949) > ttable (1.753). (3) There is a significant difference between the training methods of play and the circuit, where the practice methods of playing influence is more effective than exercise methods circuit to improving the physical fitness of students of Padang State Junior High School 9, the results show that tcount (2.779) > ttable ( 2.042).